The true confessions of Charlotte Doyle - Avi 1937- (New York Orchard Books, 1990)
As the only passenger, and the only female, on a transatlantic voyage in 1832, thirteen-year-old Charlotte finds herself caught between a murderous captain and a mutinous crew.
"Includes a new preface from Avi and a discussion guide"--Cover p. [4].
Newbery Honor Book, 1991
Keywords: Mutiny -- Fiction; Sex role -- Fiction; Self-perception -- Fiction; Ships -- Fiction; Sea stories